2015
DOI: 10.5152/tao.2015.1352
|View full text |Cite
|
Sign up to set email alerts
|

The 100 Most Cited Turkish Papers in the Otorhinolaryngology Journals of Web of Science

Abstract: Objective: The aim of the study was to analyze the 100 most cited publications with Turkish origin in the Web of Science Otorhinolaryngology (ORL) journals. Methods:The Web of Science database was searched in terms of citations for publications originating from Turkey in ORL journals since 1983. After the identification of the 100 most cited articles, analysis was performed for the first author, institution, city, publication type, subject related to subspecialty, and journals having the most cited articles. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 108 publications
1
11
0
Order By: Relevance
“…Tegobuvir (GS-9190) is a specific, covalent inhibitor of the hepatitis C virus (HCV) nonstructural 5B (NS5B) RdRp with demonstrated antiviral activity in patients with genotype 1 chronic HCV infection. [25][26][27] Our docking results showed that the hydrogen bonds involving ALA-443 and LEU-329 maintained upon the binding of Tegobuvir and SARS-CoV-2 NSP12 interface ( Figures 5A and 5C). Tegobuvir was mainly combined with the interface between SARS-CoV NSP12 and NSP7 through van der Waals potential energy and hydrophobic accumulation, involving PHE-299, PHE-727, PHE-324, PHE-325, and PHE-326 ( Figure 5E).…”
Section: Docking Results Of Tegobuvir Against Sars-cov-2 and Sars-covmentioning
confidence: 91%
“…Tegobuvir (GS-9190) is a specific, covalent inhibitor of the hepatitis C virus (HCV) nonstructural 5B (NS5B) RdRp with demonstrated antiviral activity in patients with genotype 1 chronic HCV infection. [25][26][27] Our docking results showed that the hydrogen bonds involving ALA-443 and LEU-329 maintained upon the binding of Tegobuvir and SARS-CoV-2 NSP12 interface ( Figures 5A and 5C). Tegobuvir was mainly combined with the interface between SARS-CoV NSP12 and NSP7 through van der Waals potential energy and hydrophobic accumulation, involving PHE-299, PHE-727, PHE-324, PHE-325, and PHE-326 ( Figure 5E).…”
Section: Docking Results Of Tegobuvir Against Sars-cov-2 and Sars-covmentioning
confidence: 91%
“…[11][12][13][14][15] In the publications from Turkey in the field of otolaryngology, the articles which were most cited were seen to be mostly otology and rhinology. 2,3 The reason for the highest number of pediatric studies was considered as the most widely accepted journal in this study was the International Journal of Pediatric Otorhinolaryngology. With the increased importance of gaining citation points in the new criteria for associate professorship, authors have tended towards areas where more articles have been published and where they will be able to be cited.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been previous studies containing evaluations of the number of citations, the current study is the first to have evaluated the number of authors and their institutions. 2,3…”
mentioning
confidence: 99%
“…Evaluation of the 100 most cited otolaryngology articles published from Turkey showed that they were predominantly otology. 4 As the field of otology within otolaryngology includes diseases for which the etiology and treatment has still not been clearly resolved, this has attracted the attention of researchers. Areas open for development such as congenital and acquired hearing losses, ototoxicity, tinnitus, dizziness, facial nerve diseases, and cochlear implant and newly developed endoscopic ear surgeries have led to an intensification in the field of otology.…”
Section: Discussionmentioning
confidence: 99%
“…Anah tar Ke li me ler: Akademik ilerleme; bibliyometrik; Türkiye; yayınlar and the number of authors. [3][4][5] In a general sense, science is a universal case and there is not expected to be a difference. The aim of this study was to compare and reveal any differences between articles written by Turkish authors in the field of otolaryngology, which have been accepted for publication in national journals in the last 6 years, and international articles in the Science Citation Index (SCI) category.…”
mentioning
confidence: 99%